The Implementation of Covid-19 Archives Preservation in College - Lolytasari Lolytasari; Hikmah Irfaniah (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: Circular Letter No. 62 of 2020 concerning the Preservation of Covid-19 handling archives is a public policy that needs to be implemented by State Universities as part of government agencies. Purpose: This study aims to explore efforts to implement policies to preserve the records of Covid-19 handling at university and understand the challenges it faces as university that does not have its own Archive yet. Method: This study uses a qualitative approach with a case study method. There are three informants selected through the purposive sampling method. Informants were selected based on the following criteria: 1) has mandatory duties in archival activities and 2) positioned as an archivist. Research data obtained through interviews and documentation studies Findings: The university efforts in preserving Covid-19 handling archives are carrying out internal communication to preserve archives within the General, increasing archivists’ competencies and knowledge, and conducting from preparation to Covid-19 archives assessment. Related efforts in the organizational structure have not been made because this process takes a long time. The challenges arise from the lack of human resources in every unit of PTN X and the absence of an archival institution which makes it difficult to implement implementation in all units of university Conclusion: The university has made efforts to preserve the handling of Covid-19 within the smaller scope, the General Bureau. For a wider scope, the implementation has not been carried out due to lack of human resources and the absence of university Archive owned by university. Keywords: archives preservation, Covid-19 archives, public policy, university archives